Passing return to sports tests after ACL reconstruction is associated with greater likelihood for return to sport but fail to identify second injury risk - Welling, W.; Benjaminse, A.; Lemmink, K.; Gokeler, A. (The Knee, 2020)
A limited number of patients return to sport (RTS) after an anterior cruciate ligament reconstruction (ACLR) and patients who RTS have a relatively high risk for second ACL injury. The purpose of the current study was to compare the results of a test battery between patients who returned to the pre-injury level of sport (RTS group) and patients who did not (NO-RTS group).